Treatability of Petrochemical Waste Using a Pilot Scale SBR System - Parviz Monajemi; Hassan Kazemi (آب و فاضلاب, 2005)
This study was carried out to investigate treatability of the effluent from Ammonium Nitrate Unit at Shiraz petrochemical complex via a sequencing batch reactor (SBR) system. The study included six months of data collection on petrochemical wastes treatability and characterization of the effluent from Ammonium Nitrate unit and four months of pilot scale lab experiments. Qualitative experiments showed that the effluent contained high Ammonia and Ammonium Nitrate but no essential nutrients or minerals. Pilot scale laboratory modeling with four 4-liter reactors containing different loading schemes was used. In the preliminary phase, the high pH value of the effluent (about 11) was reduced to normal using H3PO4. To supply the nutrient, CH3OH and K2HPO4 were used as C and P sources, and mineral materials such as NaCl, MgSo4 and CaCl2 were added. The acclimation process took about 40 days. In the pilot scale treatability experiments, the optimum sludge to waste ratio was calculated, and using this ratio, various retention times for aerobic and anaerobic phases were tested to determine the optimum retention time for these phases. The results show that the Ammonium Nitrate unit effluent at Shiraz Petrochemical Complex is biologically treatable. The application of SBR system fits well with an efficiency of 97% in Ammonia and Ammonium nitrate removal. The Ammonia and Ammonium Nitrate concentrations are found to less than 100mg/l.